Koroško mežiško narečje v luči novih glasoslovnih raziskav - Zorko, Zinka (Slavia Centralis, 2020)
The Carinthian Mežica Dialect in View of Recent Phonological Studies This paper presents new phonological studies of the Carinthian Mežica dialect. In Javorje, Črna and in Mežica, long diphthongs changed into monophthongs; Kotlje and Pameče retained the typically Charinthian diphthongal-monophthongal system, Ojstrica retained the Podjuna dialect, and the Mislinja local dialect has the Styrian vowel system typical of southern Pohorje.